(untitled) (International Journal of Ayurveda and Pharma Research, 2024)
Introduction: Ayurveda describes local minor diseases in detail along with systemic diseases. Cosmetic diseases are those that impact a person’s emotional, psychological, and social well-being. In Ayurveda, Darunaka, a cosmetic ailment, is referred to as either Kapalgat Roga or Kshudra Roga. Darunaka is a safe substance that doesn’t hurt, but it might cause psychological tension and low self-esteem. Everyone is highly aware of the importance of hair care, and according to Ayurveda, Darunaka is one of the main causes of hair loss. Darunaka is the Ayurvedic term that most closely correlates seborrhoeic dermatitis and dandruff (pityriasis capitis). Few explorations have been conducted regarding above, but no one has covered all aspects comprehensively thus this paper aim to collect and comprehensive review information available regarding about Darunaka and to understand its relevance in present era and preventive care. Methodology: This review is in a narrative format and done from literature and publications relevant to Darunaka Vyadhi and dandruff. Results: According to Vagbhata the prognosis of Darunaka is included in Sadhya stage. This literature review includes pathogenesis, contributing factors, management of Darunaka as per Ayurveda. These basic principles of the Vyadhi are still applicable and it improves the quality of life of the patient. There’s a good chance that Darunaka’s Ayurvedic care will unravel the disease’s pathophysiology. Discussion: The discussion is mainly based on conceptual part and the effect is made to draw a final conclusion.